The impact of psychological stress on immune function in the athletic population - Clow, A.; Hucklebridge, F. (Exercise Immunology Review, 2001)
In many ways, the physiological and immune consequences of acute bursts of physical exercise parallel the effect of an acute psychological stressor. Similarly, the net effects of endurance training resemble chronic psychological stress, whereas the physiological milieu associated with overtraining resembles that of melancholic depression. We suggest that the prolonged psychological stress often associated with athletic training and competition may make athletes more vulnerable to the negative health effects of training. Furthermore, a relationship between anxiety and life events on susceptibility to injury is well documented. Individual differences in self-confidence and self-esteem are also known to relate to the occurrence of injury as well as recovery from injury. We suggest that these two observations may be linked. It is the purpose of this paper to review the most recent evidence that psychological stress does impact upon the balance of the immune system in such a way as to be relevant to health outcomes and that the athletic population, in particular those with low self-esteem, may be especially vulnerable due to the probable synergistic effects of both physical and psychological stress.